2000
DOI: 10.1002/1521-3773(20001215)39:24<4615::aid-anie4615>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Phenylaziridine as a Masked 1,3 Dipole in Reactions with Nonactivated Alkenes

Abstract: Really a carboamination, that is the end result of the reaction of N‐tosyl‐2‐phenylaziridine (1) with various alkenes in the presence of BF3⋅Et2O to produce substituted pyrrolidines. With methylenecycloalkenes such as 2, the spiropyrrolidine 3 is conveniently accessible in good yields. In these reactions 1 has the reactivity of an electron‐poor 1,3 dipole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Notably, the lack of minor product formation under experimental conditions reiterates the importance of incipient carbocationic stabilization by the presence of phenyl or aryl rings in the aziridine molecule. 29 The stability enjoyed by the incipient carbocation from the presence of a -Ph group is critical for the excellent regioselectivity, since alkyl substituted aziridines have been reported to exhibit poor regioselectivity under Lewis-acid mediated-or catalysed conditions. 30 Given the discussed stability of the phenyl substituted carbon, it can be hypothesized that the incorporation of more electron donating groups at the para-position of the phenyl ring will increase the incipient carbocationic stability, 31 thus increasing the rate of the ringopening process.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the lack of minor product formation under experimental conditions reiterates the importance of incipient carbocationic stabilization by the presence of phenyl or aryl rings in the aziridine molecule. 29 The stability enjoyed by the incipient carbocation from the presence of a -Ph group is critical for the excellent regioselectivity, since alkyl substituted aziridines have been reported to exhibit poor regioselectivity under Lewis-acid mediated-or catalysed conditions. 30 Given the discussed stability of the phenyl substituted carbon, it can be hypothesized that the incorporation of more electron donating groups at the para-position of the phenyl ring will increase the incipient carbocationic stability, 31 thus increasing the rate of the ringopening process.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, the transition‐metal‐catalyzed [3+2] cycloadditions of aziridines represent powerful tools enabling quick and efficient access to pyrrolidines in an atom‐economical fashion. However, almost all previous studies on this topic have been focused on 1,3‐dipolar cycloadditions of either aryl or alkyl aziridines by selective C−C, and C−N bond cleavage with alkynes or alkenes for the formation of pyrrolidine derivatives, substituted with saturated C−C bonds, in racemic form. In contrast, the [3+2] cycloaddition of an aziridine with an allene is rarely reported, and seriously limits the utilization of this method in the synthesis of the valuable 2‐methylene‐ and 3‐methylene‐pyrrolidines containing a C=C bond .…”
Section: Figurementioning
confidence: 99%
“…[180] Also in 1999, Mann and co-workers used the same catalyst for the intermolecular cycloaddition of arylsubstituted aziridines with enol ethers, [181] and later demonstrated that this system could also be applied to non-activated alkenes (Scheme 7.28, B). [182] In these early works, high diastereoselectivity could be achieved only in the case of the formation of bicyclic five-five ring systems. In 2000, Nakagawa and Kawahara then reported the scandium-catalyzed cycloaddition of unsubstituted Cbz protected aziridines with skatole and used the method in a formal synthesis of physostigmine (Scheme 7.28, C).…”
Section: Formal [3+1] Cycloadditionsmentioning
confidence: 99%